2015
DOI: 10.1089/aid.2015.0062
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Associated with Race/Sex Disparities in Diabetes and Hypertension Prevalence, But Not Cardiovascular Disease, Among HIV-Infected Adults

Abstract: Race/sex differences are observed in cardiometabolic disease (CMD) risk and prevalence in the context of treated, chronic HIV infection, and these differences could be exacerbated by disparities in obesity prevalence. We sought to determine the effect of obesity on these disparities among people living with HIV. Prevalence of CMD (dyslipidemia, cardiovascular disorders, hypertension, diabetes, chronic kidney disease) was determined for patients seen at the University of Alabama at Birmingham HIV clinic between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 44 publications
5
24
0
Order By: Relevance
“…In previous work by our group and others, obesity contributes to the excess prevalence of cardiometabolic diseases, and obesity and excess adiposity more commonly affect women than men [6], [7], [8]. Black women in particular have a 2-fold increase in hypertension and diabetes compared to other groups, an association that was attenuated after adjusting for obesity [8]. Our data confirm previous reports that women living with HIV (WLH) are more likely to be obese than men and at particular risk for poor health outcomes related to obesity [7], [9], [10].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In previous work by our group and others, obesity contributes to the excess prevalence of cardiometabolic diseases, and obesity and excess adiposity more commonly affect women than men [6], [7], [8]. Black women in particular have a 2-fold increase in hypertension and diabetes compared to other groups, an association that was attenuated after adjusting for obesity [8]. Our data confirm previous reports that women living with HIV (WLH) are more likely to be obese than men and at particular risk for poor health outcomes related to obesity [7], [9], [10].…”
Section: Introductionmentioning
confidence: 74%
“…Unfortunately, chronic HIV infection is associated with excess risk for cardiometabolic diseases including diabetes, hypertension, dyslipidemia, and atherosclerosis [1], [2], [3], [4], [5]. In previous work by our group and others, obesity contributes to the excess prevalence of cardiometabolic diseases, and obesity and excess adiposity more commonly affect women than men [6], [7], [8]. Black women in particular have a 2-fold increase in hypertension and diabetes compared to other groups, an association that was attenuated after adjusting for obesity [8].…”
Section: Introductionmentioning
confidence: 84%
“… After initiating ART, approximately one‐third to one‐half of HIV‐infected adults are overweight or obese, and obesity is more prevalent in HIV‐infected women than in HIV‐infected men. Our data, when examined in conjunction with this evidence, suggest that structured, evidence‐based interventions designed to lower carbohydrate and increase protein consumption may help to mitigate the rising obesity epidemic in HIV‐infected adults.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Seven studies investigating CVD incidence and prevalence in mixed-sex cohorts, all found increased cardiovascular events in HIV-positive men when compared to WLHIV. [14][15][16][17][18][19][20] However, the three that compared these data to data from HIV-negative populations (one using an HIV-negative comparison group, the other two referring to general population data) found that the increased prevalence of cardiovascular events seen among PLWH was more pronounced in female study participants, suggesting that the increased risk of CVD conferred by HIV may be even higher in women. [15,17,19] 3.2 Pathogenesis of CVD in women living with HIV In studies directly comparing HIV-positive men and women, men have been found to be at greater risk of increased carotid intimal thickness (cIMT) and coronary artery stenosis ( Table 2).…”
Section: Epidemiology Of Cvd In Women Living With Hivmentioning
confidence: 99%
“…Eleven studies assessed the prevalence of traditional CVD risk factors (such as hypertension, diabetes mellitus and obesity) among WLHIV (Table 3). [16,[34][35][36][37][38][39][40][41] Studies conducted in a variety of geographical regions found that WLHIV were significantly more likely to have a raised body mass index when compared to HIV-positive men, [37,39,41] or HIV-negative women. [30] Metabolic syndrome (MS) also appears to be more prevalent in WLHIV, with studies from Uganda and France finding an association between female gender and MS. [35,39] Seven studies investigated the Framingham Risk Score (FRS) scores of people living with HIV, with differing results.…”
Section: Traditional Risk Factors For Cvdmentioning
confidence: 99%